1996
DOI: 10.1002/(sici)1097-0185(199605)245:1<13::aid-ar3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of melatonin in the harderian gland of Syrian hamster

Abstract: Background The Harderian gland (HG) is a tubulo‐alveolar gland found within the ocular orbit of animals which present a nictitating membrane. The Harderian gland is regarded as an extrapineal melatonin producing organ and both, photoperiod and melatonin have been shown to exert an important role in the metabolism and morphological features of such a gland. Our results seem to support the presence of melatonin in the nuclei of the HG cells, although our studies have not definitively proved such presence. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
2
7
0
2
Order By: Relevance
“…The kinetic values for 125 I‐melatonin binding determined in this study are consistent with previous immunocytochemical studies by light [27, 28] and electron [21] microscopy suggesting the existence of a nuclear receptor for melatonin. Moreover, the data of this study agree with previous findings demonstrating the nuclear localization of melatonin in several tissues including harderian glands.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The kinetic values for 125 I‐melatonin binding determined in this study are consistent with previous immunocytochemical studies by light [27, 28] and electron [21] microscopy suggesting the existence of a nuclear receptor for melatonin. Moreover, the data of this study agree with previous findings demonstrating the nuclear localization of melatonin in several tissues including harderian glands.…”
Section: Discussionsupporting
confidence: 90%
“…Whether these effects of melatonin (calendar information and/or antioxidant role) occur into the harderian glands directly or indirectly through other factors is yet unknown. Although melatonin is a small, highly lipophilic molecule that easily passes through biological membranes, data on its subcellular distribution and nuclear binding sites of melatonin in harderian glands are scarce [21]. Some studies show melatonin binding to crude membrane preparations from harderian glands of Syrian hamsters [22, 23] but none of them satisfied the pharmacokinetic properties of high affinity receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear location of ASMT in spermatocytes, detected by immunohistochemistry in this study, was corroborated by the analysis of the sheep ASMT sequence (cNLS Mapper, (Kosugi et al, 2009b)), which predicted a bipartite nuclear localization signal within the terminal 60amino-acid region compatible to both nuclear and cytoplasmic location of the protein (Kosugi et al, 2008(Kosugi et al, , 2009a. Melatonin has also been previously identified in the nucleus of the harderian gland of Syrian hamster (Coto-Montes et al, 1996). Therefore, the melatonin produced by the ASMT located in the nuclei of spermatocytes may protect the DNA from apoptosis and ROS damage during meiotic divisions.…”
Section: Discussionsupporting
confidence: 81%
“…By analogy, a similar hypothesis can be proposed for the intracellular sites of 5-HT/melatonin synthesis in the Harderian gland, since lipid vacuoles, smooth endoplasmic reticulum and mitochondria are well represented in the type I cells of the gland. Recently, Coto-Montes et al (1996) have shown, using the ABC method, that immunoreactive melatonin is present in all cell types of the male Syrian hamster Harderian gland. This suggests that melatonin produced by type I cells probably acts on type II cells (paracrine effect of melatonin).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous immunohistochemical studies have shown the presence of melatonin in the rodent Harderian gland (Bubenik et al 1976a(Bubenik et al , b, 1978Vivien-Roels et al 1981;Coto-Montes et al 1996), the cell type in which indoleamine synthesis occurs remains unknown. The purpose of the present study has therefore been to determine the presence and localization of cells immunoreactive for serotonin (5-HT; a melatonin precursor) and/or tryptophan hydroxylase (TPH; the rate-limiting enzyme for 5-HT synthesis) in male Wistar rats, Syrian hamsters and Djungarian hamsters.…”
Section: Introductionmentioning
confidence: 95%